Signal content of red facial coloration in female mandrills (Mandrillus sphinx) - Setchell, J.M.; Wickings, E.J.; Knapp, L.A. (Proceedings of the Royal Society B: Biological Sciences, 2006)
Studies of secondary sexual ornamentation and its maintenance by sexual selection tend to focus on males; however, females may also possess showy ornaments. For example, female mandrills possess facial coloration that ranges from black to bright pink. We used fortnightly photographs of 52 semi-free-ranging females aged above 3years over 19 months to evaluate whether colour conveys information concerning female competitive ability, reproductive quality, age or reproductive status. Colour was not related to female rank or quality (body mass index, age at first birth or mean inter-birth interval); however, colour did increase significantly with age and primiparous females were darker than multiparous females. Colour may therefore signal reproductive quality, as younger females are less fertile and produce smaller offspring. Colour was brighter during the follicular phase than during the luteal phase, suggesting that it may signal fertility. Colour also varied across gestation and peaked at four and eight weeks post-parturition, suggesting that it may signal approaching parturition and lactation. Future studies should examine the relationship between colour and the menstrual cycle in more detail, the hormonal basis of female colour, and determine experimentally whether mandrills of both sexes attend to differences in colour between and within females.
EPrint Processing Status: Author unable to supply full text
Keywords: Sexual skin; Sexual selection; Secondary sexual ornaments; Signals.